Ballistic spin filtering across the ferromagnetic-semiconductor interface - Li, Y.H. (Condensed Matter Physics, 2012)
The ballistic spin-filter effect from a ferromagnetic metal into a semiconductor has theoretically been studied with an intention of detecting the spin polarizability of density of states in FM layer at a higher energy level. The physical model for the ballistic spin filtering across the interface between ferromagnetic metals and semiconductor superlattice is developed by exciting the spin polarized electrons into n-type AlAs/GaAs superlattice layer at a much higher energy level and then ballistically tunneling through the barrier into the ferromagnetic film. Since both the helicity-modulated and static photocurrent responses are experimentally measurable quantities, the physical quantity of interest, the relative asymmetry of spin-polarized tunneling conductance, could be extracted experimentally in a more straightforward way, as compared with previous models. The present physical model serves guidance for studying spin detection with advanced performance in the future.